Both alpha and beta chains of HLA-DC class II histocompatibility antigens display extensive polymorphism in their amino-terminal domains. - Schenning, L (1984)
At least three class II antigens, all composed of an alpha and a beta subunit, are encoded in the human major histocompatibility complex, i.e., DR, DC and SB. Two cDNA clones, encoding a DC alpha and a DC beta chain, respectively, were isolated from a cDNA library of the lymphoblastoid cell line Raji (DR3,w6). The two polypeptides predicted from the nucleotide sequences of these clones are each composed of a signal peptide, two extracellular domains, a hydrophobic transmembrane region and a short cytoplasmic tail. Comparison of the DC alpha sequence with two previously published partial sequences shows that the majority of the differences is located in the amino-terminal domain. The differences are not randomly distributed; a cluster of replacements is present in the central portion of the amino-terminal domain. Likewise, the allelic polymorphism of the DC beta chains occurs preferentially in the amino-terminal domain, where three minor clusters of replacements can be discerned. The non-random distribution of the variability of DC alpha and beta chains may be due to phenotypic selection against replacement substitutions in the second domains of the polypeptides.